Triphenylamine‐Functionalized Metal Nanoclusters for Efficient and Stable Perovskite Solar Cells - Lin Wang; Jieru Du; Jiahao Wu; Zi‐Ang Nan; Simin Li; Xiongkai Tang; Zhenlang Xie; Qinghua Xu; Xuekun Gong; Jinlu He; Ruihao Chen; Nanfeng Zheng; et al. (Advanced Science)
Abstract Reported herein is a ligand engineering strategy to develop photoelectric active metal nanoclusters (NCs) with atomic precision. Triphenylamine (TPA), a typical organic molecule in the photoelectric field, is introduced for the first time to prepare atomically precise metal NCs that prove effective in the fabrication of perovskite solar cells (PSCs). The scalable synthetic prototype, unique electronic strucuture, and atomically precise structure of the cluster ([(AgCu)37(PPh3)8(TPA‐C≡C)24]5+) are illustrated in this work. When being employed as a buffer layer in the perovskite/HTL interface of PSCs, significantly enhanced performance is observed. The resultant n‐i‐p devices achieved a substantial power conversion efficiency as high as 25.1% and long‐term stability. The findings offer valuable insights into preparing functionalized metal NCs that play multiple roles in improving the performance of the device: while the inorganic metal core enhances conductivity, the organic TPA shell promotes the “carrier transfer” between the perovskite and HTL layer and prevents the perovskite from corrosion.